The contribution of urban public space to the social interactions and empowerment of women - Alizadeh, Hooshmand; Kohlbacher, Josef; Bork-Hüffer, Tabea; Mohammed-Amin, Rozhen Kamal; Kiomars, Naimi (Journal of urban affairs, 2024)
Public spaces are central to social interactions and cohesion, overall urban life, and therewith sustainable urban development. They can play key roles in increasing social interactions and women’s empowerment. The literature lacks empirical research on the state of women’s use of public spaces and these spaces’ effects on women’s social interactions and empowerment in Middle Eastern cities in the Kurdistan Region, where women historically enjoyed greater freedom. This paper addresses this gap by presenting insights from a comparative cross-border study with women in two Kurdish cities, Sanandaj and Sulaimani. In doing so, the paper contributes an empirically based theorization of urban public place-making, and debates its effects on the empowerment of women in the context of Kurdish urbanisms. The study developed a survey instrument to measure women’s interactions with and in public spaces and their related empowerment in these two cities across five main factors. Despite the local women’s limited interaction with and in the public spaces of these two Kurdish cities, the findings show a strong positive relationship between women’s interactions in public spaces and their empowerment. The results also suggest that socio-political and related socio-spatial changes have contributed to a decreased relevance of traditional meeting and leisure spaces but have increased the use of malls as commodified spaces, particularly in Sulaimani. The study debates the specificities of urban public spaces in Kurdish cities, and commonalities as well as differences compared with developments elsewhere.
Gesehen am 11.04.2025
Online veröffentlicht: 26. September 2022